Penerapan Tema Arsitektur Modern Pada Perancangan Kompleks Perumahan Di Lambaro Kab Aceh Besar - lukmanul lukman hakim (Universitas Syiah Kuala, 2020)
AbstractHousing is a group of houses that functioned as residential neighborhood environment equipped with environmental infrastructure and facilities [1], with the increase of population will be increased housing demand. To meet the level of housing needs a place that provides a residential units, and supporting facilities in it. Based on this matter, it is needed a design that provide of housing in lambaro, Aceh Besar. the design of residential in lambaro, Aceh Besar is designed using the theme of Comfort (comfortable) which uses the approach of the theory of